The Influence of Workload, Work Stress and Employee Voice on Performance Assessment with Work Motivation as Intervening at PT Pelabuhan Indonesia (Persero) Regional 1 Dumai - Ikazurry Mutia; M. Chaerul Rizky; Sri Rahayu (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to analyze the influence of Workload, Work Stress, and Employee Voice on Performance Assessment with Work Motivation as an intervening variable in PT Pelabuhan Indonesia (Persero) Regional 1 Dumai. The port industry has operational characteristics with a high level of complexity, so effective human resource management is the key to the success of the organization in providing optimal port services. This study uses a quantitative approach with a survey method using questionnaires as a data collection instrument. The data analysis technique uses Structural Equation Modeling (SEM) based on Partial Least Square (PLS) through the SmartPLS application to test the direct and indirect relationships between the research variables. The results of the study showed that all ten hypotheses proposed were accepted and proven to be statistically significant. Workload has a positive and significant effect on Work Motivation and Employee Performance Assessment. Employee Voice has been proven to have a positive and significant effect on Work Motivation with the highest level of significance, as well as a significant effect on Performance Assessment. Work Motivation has a positive and significant effect on Performance Assessment with the greatest power of influence. Work Stress has a positive and significant effect on Work Motivation and Performance Assessment. Mediation effect testing proves that Work Motivation plays a significant role as an intervening variable that connects Workload, Employee Voice, and Work Stress with Performance Appraisal.